About a Silent Piano and the Violinist on the Roof. “L’Om Dada” – a Survivance throughout a Century - POENAR, Aura (Studia Universitatis Babeș-Bolyai Dramatica, 2016)
Dada has marked a radical shift in what our idea of harmony and consonance told us how to make sense of art. No longer functional in a traditional, mimetic dimension, the art of the avant-garde does not seek to gratify and reassure the viewer, but involves him actively as it constantly defamiliarizes its objects. Our paper analyzes Gigi Căciuleanu’s performance l'Om DAdA in conjunction to the movements of contemporary art under the continuous influence and guidance of the early Dada principles and strategies. We thus observe how the narrative of the performance builds on the fractures and discontinuities of space, history, movement in a dialogue that arches over a century with the Dada artistic phenomenon and mindset. Căciuleanu’s choreographic theatre performs a mapping of our Real revisiting Dada’s answer to a world already dislocated by the historical events of the 20th century. Taking Tristan Tzara’s text L’homme approximatif, Gigi Căciuleanu takes it apart and puts it back together in a discontinuous montage which reflects on the dislocation of our own world.